Faktor-faktor yang berhubungan dengan kejadian malaria Kecamatan Tanjung Tiram Kabupaten Batubara tahun 2023 - Khodijah Tussolihin Dalimunthe; Tina Meirindany; Mutiara Nauli (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Malaria is an infectious disease transmitted to humans by the bite of a female Anopheles mosquito infected with a protozoan parasite of the genus Plasmodium. One of the determinants of the spread of malaria by the host is community knowledge and the behavior of using house wire screens. his type of quantitative research is with a cross-sectional design and will be carried out from April to June 2023 in Hamlet XII, Suka Maju Village, Tanjung Tiram District, Batubara Regency. The research sample was 72 respondents with a purposive sampling technique. Test analysis using chi-square and simple logistic regression. The results showed that there was a relationship between the two categories studied <0.05. There is a relationship between the use of wire gauze and the incidence of malaria with a value of p=0.004, as well as a relationship between knowledge and the incidence of malaria with a value of p=0.03. The incidence of malaria that occurred in Batu Bara was due to knowledge and behavior factors of not using wire mesh at home. It is necessary to carry out counseling about malaria and the importance of using wire gauze.